Management of Tuberculous Cutaneous Fistula - Massamba Miabaou Didace; Lenga Loumingou Ida; Ondima Irène; Peko Jean Félix (Case Reports in Surgery, 2020)
Tuberculosis is an endemic emergency that is prevalent in developing countries, particularly in sub-Saharan Black Africa, including Congo-Brazzaville. In addition to the pulmonary, ganglionic, and bone forms, there are other poorly documented locations. In the Congo, among these is cutaneous tuberculosis which is exceptional. A 9-year-old boy and two adult patients had persistent lesions of the left hip and thigh wounds, chest wall, and hypogastric wound with no healing for more than four months, respectively. Among these patients, one case of tuberculous contact was noted. Histopathological examination revealed a Koester follicle, suggesting a tuberculous skin fistula. A fistulectomy was performed, coupled with a quadruple antituberculous therapy combining rifampicin, isoniazid, ethambutol, and pyrazinamide for two months, relayed by a dual therapy consisting of isoniazid and ethambutol for 6 to 8 months. The evolution was favorable in all cases with healing of the lesions after 3 to 6 weeks. The existence of inexhaustible fistulas and the absence of scarring of a wound should make one suspect, among other things, cutaneous tuberculosis. The product of fistulectomy makes it possible to establish the histological diagnosis of cutaneous tuberculosis.